Data for "Factor Structure and Psychometric Properties of the German Version of the Family Expressiveness Questionnaire – the FEQ-GR" - Zehtner, Raphaela Isabella; Bäurle, Cosima L.; Walter, Bertram; Stark, Rudolf; Hermann, Andrea; Justus Liebig University Giessen (My University, 2021)
Raw data, analysis syntax/code and output for the translation, construction and validation of the Familiy Expressiveness Questionnaire (FEQ-GR).
Keywords: family expressiveness; assessment; factor structure; validation